Gut Microbiota: Novel Therapeutic Target of Ginsenosides for the Treatment of Obesity and Its Complications - Zhuang, Tongxi; Li, Wei; Yang, Li; Wang, Zhengtao; Ding, Lili; Zhou, Mingmei (Frontiers in Pharmacology, 2021)
Obesity, generally characterized by excessive lipid accumulation, is now a metabolic threat worldwide due to its rapid growth in global prevalence. Ginsenosides are crucial components derived from natural plants that can confer metabolic benefits for obese patients. However, it is difficult for ginsenosides to be directly absorbed into blood circulation because most of them are metabolized or transformed when they enter the intestine, which obscures the specific mechanisms needed to improve obesity outcomes. Recently, studies have indicated that ginsenoside intervention has beneficial metabolic effects on obesity because it allows for the dysbiosis of gut microbiota in regulating the secretion of endogenous metabolites, and because it restores the intestinal mucosal barrier. In this review, we summarize the role of gut microbiota in the pathogenetic process of obesity, and explore the mechanism of ginsenosides for improving obesity (i.e., they modulate the composition of gut microbiota). Ginsenosides are expected to become a promising anti-obesity medical intervention in the future.